Involvement of a large plasmid in the degradation of 1,2-dichloroethane by Xanthobacter autotrophicus. - Tardif, G (1991)
Xanthobacter autotrophicus GJ10 is a bacterium that can degrade short-chain halogenated aliphatic compounds such as 1,2-dichloroethane. A 200-kb plasmid, pXAU1, was isolated from this strain and shown to contain the dhlA gene, which codes for haloalkane dehalogenase, the first enzyme in the degradation pathway of 1,2-dichloroethane by GJ10. Loss of pXAU1 resulted in loss of haloalkane dehalogenase activity, significantly decreased chloroacetaldehyde dehydrogenase activity, and loss of resistance to mercuric chloride but did not affect the activity level of haloalkanoate dehalogenase, the second dehalogenase in the degradation of 1,2-dichloroethane.